PENGARUH SELF-REGULATED LEARNING DAN MOTIVASI BELAJAR TERHADAP PROKRASTINASI PENYUSUNAN SKRIPSI PADA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN UNIVERSITAS NEGERI SURABAYA - Wulan Suci Maghfiroh; Durinda Puspasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Procrastination in thesis writing remains a common issue among students, as it can hinder the completion of their studies. This study aims to analyze the influence of self-regulated learning and learning motivation on thesis-writing procrastination among Office Administration Education students at the State University of Surabaya. This study employs a quantitative explanatory approach with a population of 186 students from the 2022 cohort. A sample of 127 respondents was determined using the Slovin formula with a proportional random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that self-regulated learning has a negative and significant effect on thesis-writing procrastination (t = -3.312; sig = 0.001), learning motivation has a negative and significant effect on thesis-writing procrastination (t = -5.461; sig = 0.000), and both variables simultaneously have a significant effect on thesis-writing procrastination (F = 34.576; sig = 0.000), contributing 35.8 percent to the variance. These findings confirm that strengthening self-regulation skills and learning motivation can reduce students' tendency to procrastinate during the thesis-writing process